Improving Understanding Of Muslim-Friendly Tourism Village Management In Indonesia Through Socialization and Education - Hermawan Adinugraha, Hendri; Suroso; Slamet Nurchamid; Moh. Nasrudin; Maulana, Asep Suraya (Amala Jurnal Pengabdian Kepada Masyarakat, 2025)
This community service program aims to improve understanding of Muslim-friendly tourism village management in Indonesia through socialization and education. Muslim-friendly tourism villages have great potential in the halal tourism industry but still face challenges, such as limited understanding of halal standards, lack of supporting facilities, and lack of digital-based marketing strategies. To overcome these problems, this program adopts socialization, education, and mentoring methods involving local stakeholders. Socialization is conducted through interactive discussions and seminars, while education includes technical training for tourism actors related to halal service management and digital marketing. The program evaluation showed a significant increase in community understanding of halal tourism, readiness for Muslim-friendly accommodation, and the number of businesses applying for halal certification. The program contributes to strengthening the capacity of tourism village managers to provide Sharia-based services and increase attractiveness for Muslim tourists. Continuous assistance is needed to ensure the sustainability of the implementation of the halal tourism concept in various tourism villages in Indonesia.